IMPLEMENTASI PELAKSANAAN RESTRUKTURISASI PEMBIAYAAN BERMASALAH DALAM UPAYA SUSTAINABLE BANKING DI BANK SYARIAH INDONESIA - Syariah, Emy; Isfandayani, Isfandayani (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2024)
This research aims to determine the implementation of restructuring of problematic financing and whether the implementation of restructuring can strive for sustainable banking. This research uses a descriptive method with a qualitative approach. The author collected data using observation, interviews, and documentation methods from three informants in the Marketing Division, with the research location at Bank Syariah Indonesia KCP Bekasi Square. The results of this research show that: 1. The implementation of the restructuring of problematic financing that Bank Syariah Indonesia KCP Bekasi Square has carried out is effective as a form of rescue for problematic financing customers. OJK's restructuring policy is the best step in dealing with problematic financing. 2. The implementation of restructuring to sustain banking has had a very positive impact, such as the bank's performance becoming healthy and the portfolio and customer collectibility returning to normal by integrating environmental, social and governance criteria. This restructuring implementation can support sustainable banking at Bank Syariah Indonesia KCP Bekasi Square.